Meta-analysis of immunonutrition in major abdominal surgery - Probst, Pascal; Ohmann, Steffen; Klaiber, Ulla; Hüttner, Felix; Billeter, Adrian; Ulrich, Alexis; Büchler, Markus W.; Diener, Markus K. (The British journal of surgery, 2017)
Background: The objective of this study was to evaluate the potential benefits of immunonutrition in major abdominal surgery with special regard to subgroups and influence of bias. Methods A systematic literature search from January 1985 to July 2015 was performed in MEDLINE, Embase and CENTRAL. Only RCTs investigating immunonutrition in major abdominal surgery were included. Outcomes evaluated were mortality, overall complications, infectious complications and length of hospital stay. The influence of different domains of bias was evaluated in sensitivity analyses. Evidence was rated according to the GRADE Working Group grading of evidence. Results A total of 83 RCTs with 7116 patients were included. Mortality was not altered by immunonutrition. Taking all trials into account, immunonutrition reduced overall complications (odds ratio (OR) 0·79, 95 per cent c.i. 0·66 to 0·94; P = 0·01), infectious complications (OR 0·58, 0·51 to 0·66; P < 0·001) and shortened hospital stay (mean difference -1·79 (95 per cent c.i. -2·39 to -1·19) days; P < 0·001) compared with control groups. However, these effects vanished after excluding trials at high and unclear risk of bias. Publication bias seemed to be present for infectious complications (P = 0·002). Non-industry-funded trials reported no positive effects for overall complications (OR 1·13, 0·88 to 1·46; P = 0·34), whereas those funded by industry reported large effects (OR 0·66, 0·48 to 0·91; P = 0·01). Conclusion Immunonutrition after major abdominal surgery did not seem to alter mortality (GRADE: high quality of evidence). Immunonutrition reduced overall complications, infectious complications and shortened hospital stay (GRADE: low to moderate). The existence of bias lowers confidence in the evidence (GRADE approach).